SELF-MANAGEMENT STRATEGIES AND THEIR EFFECTIVENESS - Sayfullokh Kozimov (Galaxy International Interdisciplinary Research Journal, 2024)
This article covers the topic of self-management strategies and their effectiveness. The research also examines the strategies used by people of different ages and professions, and examines their impact on personal and professional outcomes. The article provides information on self-management related to motivation, goal setting, time management, and stress reduction.